Green Shoots: Opportunities to grow a sustainable WA economy - Bond-Smith, Steven; Cassells, Rebecca; Duncan, Alan; Mavisakalyan, Astghik; Salazar, Silvia; Sandoval-Guzman, Maria; Seymour, Richard; Twomey, Chris (Bankwest Curtin Economics Centre, 2020)
Western Australia is at a critical juncture in developing its long-term strategy to drive economic and social progress. As the state seeks to chart a course through and beyond the COVID-19 pandemic, the case to balance future economic growth with achievable targets to reduce the state’s environmental footprint have never been more compelling.